A STUDY OF THE LI1+XTI2-XO4 SPINEL SYSTEM BY DIFFUSE-REFLECTANCE SPECTROSCOPY - Harrison, M; Edwards, P; Goodenough, J (1984)
The room-temperature diffuse-reflectance spectra of compositions within the Li1+xTi2-xO4 spinel system (0 ≤ x ≤ 1 3) show three absorption bands in the range 4000 to 48,000 cm-1. Two high-energy absorption bands correspond to charge-transfer transitions from the oxygen-2p valence band to the titanium t2g and σ* conduction bands, where the σ* band of eg character has hybridized titanium-3d and titanium-4s parentage. The absorption band arising from promotion of electrons to the empty σ* band does not alter with composition whereas the absorption band arising from promotion of electrons to the partially filled t2g band narrows as the concentration of conduction electrons in the t2g band decreases. These two high-energy absorption bands fall entirely within the ultraviolet spectral region, and the absorption edge in Li 4 3Ti 5 3O4 (x = 1 3) occurs at 24,300 cm-1 (3.02 eV). A low-energy absorption band is observed in compositions with x < 1 3 and in samples of Li 4 3Ti 5 3O4 reduced in hydrogen at elevated temperatures. This band straddles the boundary between the visible and infrared spectral regions and shifts toward lower energy as the concentration of conduction electrons in the t2g band decreases. The possible origins of the band are discussed; the argument is in favor of a d-d interband transition from states in the partially filled t2g band to states in the empty σ* band. © 1984.